Stercorarius parasiticus (Stercorariidae) - Verleiten - Heinz Sielmann (IWF (Göttingen), 1978)
(en)In the present film open air shots are shown of distraction manouvers in the parasite seagull. During these manouvers the birds simulate lameness and attempt with limping and fluttering to distract possible foes from the nest.